Strategic approach in competitive and sales workflow analysis - a case study for neural / Farah Wahida Ahmad Zulkifle - Ahmad Zulkifle, Farah Wahida (Faculty of Business and Management, 2006)
The primary objective for the research done on neural biometrics fingerprint technology is to evaluate the effectiveness of business workflow, the performance and competitiveness of other competitors within the same industry. The study is to suggest strategies based on study evaluation to improve the company overall performance, so that they can provide a better service to their customers. This study used a descriptive method whereby the present business flow was first analyzed. Competitors' profile matrix and SWOT analyses were done followed by a survey focused on neural current customers. Most of their customers seems to be satisfied with services provided by neural. The sales workflow process is able to provide a good and effective service to their customer thus reflecting a good management system. However, this alone is not enough to stay abreast of their competitors. So, a few strategies had been devised to anticipate expansion internationally, focusing on product quality, customer service, management and packaging system. They should broaden their target groups and make their product affordable and attractive by engaging expertise in the specified trade.